Advanced Imaging of Multiple Myeloma Bone Disease - Hansford, Barry G.; Silbermann, Rebecca (Frontiers in Endocrinology, 2018)
Multiple myeloma (MM), a malignancy of mature plasma cells, is the second most common hematologic malignancy and the most frequent cancer to involve the skeleton [1; 2]. Bone disease in MM patients is characterized by lytic bone lesions that can result in pathologic fractures and severe pain. While recent advances in MM therapy have significantly increased the median survival of newly diagnosed patients [3], skeletal lesions and their sequelae continue to be a major source of patient morbidity and mortality and bone pain is the most frequent presenting symptom of MM patients [4]. Rapid improvements in imaging technology now allow physicians to identify ever smaller skeletal and bone marrow abnormalities, however the clinical value of subtle radiographic findings is not always clear. This review summarizes currently available technologies for assessing MM bone disease and provides guidance for how to choose between imaging modalities.